2022
DOI: 10.1538/expanim.21-0141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of HGF responses to oral traumatic ulcers using an HGF-Tg mouse model

Abstract: Hepatocyte growth factor (HGF) has been implicated in inhibiting diverse types of inflammation. Oral traumatic ulceration (OTU) is a common disease of the oral mucosa, and inflammation is the main process for ulcer healing. This study aimed to explore the expression of HGF in oral ulcers and its role in ulcer inflammation. The saliva of 14 recurrent alphous stomatitis (RAS) patients, 18 OTU patients and 17 healthy controls was collected. Traumatic ulcers of the left mucosa were observed in 42 wild-type (WT) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…HGF is a cytokine that has been shown to exert anti‐inflammatory effects in various tissues, 75–79 including the skin 80,81 and oral mucosa 82 . We previously reported that the HGF activation z‐score was higher at the plaque centre than at the periphery, which could potentially lead to central regression of the plaques 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HGF is a cytokine that has been shown to exert anti‐inflammatory effects in various tissues, 75–79 including the skin 80,81 and oral mucosa 82 . We previously reported that the HGF activation z‐score was higher at the plaque centre than at the periphery, which could potentially lead to central regression of the plaques 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that HGF inhibits p56 NF‐κB binding to the target gene promoter, suppressing NF‐κB activity, and also inhibits NF‐κB‐dependent secretion of IL‐6 induced by IL‐1β and TNF‐α in human renal epithelial cells 76 . HGF has been shown to improve oral ulcer by attenuating neutrophil infiltration in the ulcer area and suppressing proinflammatory cytokines in a mouse model 82 . Interestingly, in a psoriasis model, HGF‐overexpressing dental pulp stem cells showed an anti‐inflammatory effect with improvement of psoriatic mice skin via suppression of Th1 and Th17 and upregulation of T regs, with reduction of IFN‐γ, TNF‐α and IL‐17A and upregulation of IL‐10 80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation